Dependability engineering and complex systems : proceedings of the eleventh International Conference on Dependability and Complex Systems DepCoS-RELCOMEX. June 27-July 1, 2016, Brunów, Poland /: proceedings of the eleventh International Conference on Dependability and Complex Systems DepCoS-RELCOMEX. June 27-July 1, 2016, Brunów, Poland. (2016) - Unknown
No abstract available